Cultivos consorciados entre alface, cenoura, manjericão emelissa - Janaina Ribeiro Oliveira Fonseca (2009)
The aim of this work was to evaluate the production of phytomass andessential oil of balm (Melissa officinalis L.) and basil (Ocimum basilicum L.) in intercropped cultive. The consorted experiment was carried out from May to October of the year 2008. The experimental delimitation was randomized blocks was consisted by seven treatments and five replications. The treatments were the following intercropped yields: basil + carrot, basil + lettuce, balm + carrot and balm + lettuce and the monocultives of each medicinal plants. There had been evaluated: the production of fresh and dry phytomass and the basil and balm essential oil content. The results were submitted under a statistical analysis by the Tukey test at 5% of probability. The treatments showed significant differences: the monoculture of balm and the cultivation of intercropped balm + lettuce had the best results of fresh and dry phytomass and the highest levels of the balm essential oil cultivation, showing that the intercropped can be established between these species. For the basil, the phytomass production was higher in monoculture and the basiland lettuce intercropping, and lower in the basil and carrot one. Suchtreatments were statistically more superior than the basil and carrotintercropping. Taking this for granthed, the conclusion is that it is possible to establish an intercropping between the species used in this work.The avarage of the analyzed contrasts revealed that, for productivity featuring, the intercropping was higher both in the cultivation of basil as in the cultivation of lemon balm, and the lettuce was the best intercropping match.